A Shifting Capital of Religious Education in the Digitalization Era - Wiryadinata, Halim (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2023)
This study shows how the shifting capital of education aligns with the economic spirit in the digitalization era. The ideology of education, which supports the transformation of human resources to a better and fair world, has been shifted to the economic path due to economic and cultural triggers. The economic element shapes educational institutions' alignment in the labor market. The latter is to make the shifting capital of education move faster towards the economic demand due to the entrance of modernization culture in the form of digitalization technology. Furthermore, the development of religious education also gets the impact of digitalization era, but it still humanizes the humanity aspect as the novelty of this research. The sociological method is to be conducted to analyze and evaluate beyond the shifting capital of education. Critical thinking in the sociological method through Weberian rationality and bureaucracy is used to probe some possible answers to see the shifting capital of education. The result of this research is that the shifting capital of education toward economic and educational capitalism still upholds the humanizing humanity to work in the workforce field. The conclusion reaches that the shifting capital of education emphasizes the access of human resources to engage in the market during the digitalization era through the rationality of educational institutions.